Odpowiedzi

  • Użytkownik Zadane
2010-03-25T17:20:03+01:00
A ) 2x+y=5 /*1
2x-3y= 11

-2x-y=-5
2x-3y = 11

-2y=6 / (-2)
y=-3

b) 2x+ 7y=16 / *(-2)
4x + 3y =10

-4x -14y= -32
4x-3y=10

-17y=22 /:17
y= 22/7 (/kreska ułamkowa )
y=3 1/7

c) x+2y =-3 / * (-2)
2x-y=-1

-2x-4y =6
2x-y= -1

5y=4 /:5
y = 4/5 (/ kreska ułamkowa )
2010-03-25T17:31:47+01:00
A)
2x+y=5
2x-3y=11

y=5-2x
2x-3*(5-2x)=11

y=5-2x
2x-15+6x=11

y=5-2x
2x+6x=11+15

y=5-2x
8x=26

y=5-2x
x=3,25

y=5-2*3,25
x=3,25

y= -1,5
x=3,25


b)
2x+7y=16
4x+3y=10

x+3,5y=8
4x+3y=10

x=8-3,5y
4(8-3,5y)=10

x=8-3,5y
32-14y=10

x=8-3,5y
-14y=10-32

x=8-3,5y
-14y= -22

x=8-3,5y
y=1,57

x=8-3,5*1,57
y=1,57

x=8-5,50
y=1,57

x=2,50
y=1,57


c)
x+2y=-3
2x-y=-1/*2

X+2Y= -3
4X-2y= -2
---------------
5x= -5
x= -1

2x-y=-1
2*(-1) -y = -1
-2-y= -1
-y= -1+2
-y=1
y = -1